Physiology does not explain all sex differences in running performance - Deaner, R. O. (Medicine & Science in Sports & Exercise, 2013)
Sex differences in elite athletic performance have been of long-standing interest to physiologists. For example, the 10%-12% sex gap observed for most running world records and elite competitions spurred numerous studies on the contributors to maximal oxygen consumption (4). Moreover, the sex gap varies substantially across sports and age groups, and this variation has stimulated further physiological hypotheses. There is a potential problem, however, with using elite performances as physiological indicators: the population size of potential competitors has a massive effect on what reaches the threshold of a world record or elite performance. Thus, gender gaps in athletic performance could reflect that fewer females are competing. In conclusion, although scholars will continue to draw on sex differences in elite performances to test and generate hypotheses, the new research shows that the diversity of hypotheses can and should be expanded.